Cloud Computing Adoption in Government Agency - Azlin Khairuddin, Khairini; Fathiyah Harun, Afdallyna (International Journal of Engineering and Technology, 2018)
As accessibility to government online services is critical, MAMPU has outlined strategic directions for the implementation of Public Sector ICT. This included cloud computing adoption which aims to optimize service delivery but is progressing slowly due to resource-sharing and standardization issues. This calls for the need to assess contributing factors of technology acceptance within a public sector. Employing Malaysia NRD as a case study, we aim to identify factors of cloud adoption and determine how NRD could strategize Cloud Computing adoption. Using the DOI and TOE theories, we assessed cloud computing adoption in terms of Â¬Technology Characteristics, Organisational Readiness, and External Environment through a case study. It was found that that all constructs are significant to cloud adoption with security and service quality being the highest concern. Moreover, several elements such as compatibility, readiness and more need to be in place to enhance the impact of cloud computing adoption.Â Â